Revisiting the evidences for spectral anomalies in distant blazars: New data on the photon-ALP mixing. Issue 1 (4th August 2022) - Cenedese, Francesco; Franceschini, Alberto; Galanti, Giorgio
ABSTRACT: We re-examine possible dependencies on redshift of the spectral parameters of blazars observed at very-high energies (VHEs) with Imaging Atmospheric Cherenkov telescopes. This is relevant to assess potential effects with the source distance of the photon to axion-like particle mixing that would deeply affect the propagation of VHE photons across the Universe. We focus our spectral analysis on 38 BL Lac objects (32 high-peaked and 6 intermediate-peaked) up to redshift z ≃ 0.5, and a small sample of 5 Flat Spectrum Radio Quasars up to z  = 1 treated independently to increase the redshift baseline. The 78 independent spectra of these sources are first of all carefully corrected for the gamma–gamma interaction with photons of the Extragalactic Background Light that are responsible for the major redshift-dependent opacity effect. Then, the corrected spectra are fitted with simple power laws to infer the intrinsic spectral indices Γem at VHE, to test the assumption that such spectral properties are set by the local rather than the global cosmological environment. We find some systematic anticorrelations with redshift of Γem that might indicate, although with low-significance, a spectral anomaly potentially requiring a revision of the photon propagation process. More conclusive tests with higher statistical significance will require the observational improvements offered by the forthcoming new generation of Cherenkov arrays (CTA, ASTRI, LHAASO).